Reaction of 4-acetyl-1,2,3-triazol-5-olate with hydrazine derivatives - I. S. Khazhieva; T. V. Glukhareva; Yu. Yu. Morzherin (Chimica Techno Acta)
1,2,3-triazole attracts attention because of the ability opening ring to form α-diazoimin and intramolecular rearrangements with the formation of various heterocyclic systems. Previously the interaction of the 1H-1,2,3-triazole-5-ol sodium salt with amine hydrochloride leading to the formation of isomeric 1,2,3-triazoles was studied. In this paper we present a research of the interaction of 4-acetyl-1,2,3-triazole-5-ol sodium salt with hydrazine derivatives. As result 5-methyl-1,2,3-triazol-4-phenylcarboxamide-phenylamide and bis-5,5’-dimethyl-[1,1’]bi[[1,2,3]triazolyl]-4,4’-dicarboxylic acid derivatives were synthesized.